2015
DOI: 10.3109/13814788.2015.1046124
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards evidence-based medicine of mentors in general practice can be influenced by using medical students as academic detailers

Abstract: Knowledge and attitudes of GP mentors towards EBM can be improved by involving medical students as academic detailers. Further studies should explore the effectiveness of this method among GPs that are not mentors, and who do not have a specialization or research degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To be able to practice EBM, FPs need to have better training in research methodology principles, especially during formal medical education and postgraduate studies that also include specialization curricula. Various EBM training approaches were studied in order to encourage EBM use in physician practice [27][28][29][30][31][32][33], and they should include multifaceted, clinically integrated interventions in order to improve knowledge, skills, attitudes, and behavior amongst practicing health professionals [26]. Recently, a group of authors proposed an "EBM competency framework for real-world general practice" which has been developed out of the empirical research while taking into account the constraints of today's general practice, but further validation of this approach is needed [34].…”
Section: Knowledge Of Fps About Ebmmentioning
confidence: 99%
“…To be able to practice EBM, FPs need to have better training in research methodology principles, especially during formal medical education and postgraduate studies that also include specialization curricula. Various EBM training approaches were studied in order to encourage EBM use in physician practice [27][28][29][30][31][32][33], and they should include multifaceted, clinically integrated interventions in order to improve knowledge, skills, attitudes, and behavior amongst practicing health professionals [26]. Recently, a group of authors proposed an "EBM competency framework for real-world general practice" which has been developed out of the empirical research while taking into account the constraints of today's general practice, but further validation of this approach is needed [34].…”
Section: Knowledge Of Fps About Ebmmentioning
confidence: 99%
“…The importance of medical students' exposure to EBM was shown by Vrdoljak et al [9], who reported that knowledge and attitudes of mentors toward EBM in general practice can be influenced by using medical students as academic detailers. It has been shown that better knowledge and more positive attitudes toward EBM among medical students are associated with the exposure to the vertical subject on research in biomedicine and activities of The Cochrane Collaboration [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little evidence for success of EBM educational programs and transfer of acquired knowledge to clinical practice [ 7 ]. Practitioners often have little time to keep up with new research results and guidelines which could be implemented in practice [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%